Preventive measures for primary bloodstream infection associated with central venous catheters (Research, Society and Development, 2023)
Objective: To identify scientific studies on the importance of compliance with good nursing practices in the prevention of primary bloodstream infection related to the handling of central venous catheters. Methodology: This is an integrative literature review, searching for publications in the Medical Literature Analysis and Retrieva System On-line databases, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online and Databases of data in Nursing. Result: 19 articles were selected that made up the final sample of this literature review. For a better structural organization of the extracted results, it was decided to approach the studies according to thematic axes: safety in the insertion of the central venous catheter; knowledge and application of bundles; safety in the exchange of infusion lines and connector disinfection; safety in the preparation and administration of medicines; performing and changing dressings; sanitization of hands. Conclusion: Weaknesses were detected in the compliance of the actions of handling and maintenance of the central venous catheter, both categories present a deficit of knowledge, although the handling of the device is a routine nursing practice, it requires rigor in care in line with the safety policy of the patient.